A Performance Comparison of GaN FET and Silicon MOSFET - Khoshzaman, Shima; Hahn, Ingo (2021 22nd IEEE International Conference on Industrial Technology (ICIT), 2021)
Introducing the excellent advantages of using wide bandgap semiconductors such as gallium nitride (GaN) in the construction of the power devices has set a starting point for a new era in the history of power electronics. Replacing the silicon-based with GaN-based power devices promises a number of benefits. Higher power densities, switching speeds and temperature stabilities with lower on-state resistance, reduced conduction and switching losses and a reduction in the die size are some of the performance improvements that the GaN transistors offer. To show both the advantages and challenges regarding this new technology, the methodology for an eligible comparison between Si-based and GaN-based transistors has been explained. Experimental comparison has been performed between a 100 V commercially available enhancement mode GaN FET and two silicon-based MOSFETs, and the results are discussed in detai
Keywords: gallium nitride; silicon; wide bandgap devices; performance characterization